2020
DOI: 10.3390/antibiotics9110761
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Nurse- and Self-Administered Paediatric Outpatient Parenteral Antimicrobial Therapy

Abstract: This study aimed to compare and contrast the safety and efficacy of nurse- and self-administered paediatric outpatient parenteral antimicrobial therapy (OPAT) models of care and to identify clinical factors associated with documented adverse events (AEs). A total of 100 OPAT episodes among children aged between 1 month and 18 years who were discharged from hospital and who received continuous 24 h intravenous antimicrobial therapy at home via an elastomeric infusion device were included. All documented AEs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The rate of hospital readmissions was 5.6%, which is similar to previously published studies that have shown rates varying between 3% and 13%. 5,[9][10][11]24 Here, it must be noted that the papers reviewed for the present study focus on a single therapeutic procedure; in contrast, we analyse the overall rate of readmission without taking into account the type of disease or the procedure performed. The fact that 42% of the patients returned to HAH indicates a high degree of satisfaction with this model of care in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of hospital readmissions was 5.6%, which is similar to previously published studies that have shown rates varying between 3% and 13%. 5,[9][10][11]24 Here, it must be noted that the papers reviewed for the present study focus on a single therapeutic procedure; in contrast, we analyse the overall rate of readmission without taking into account the type of disease or the procedure performed. The fact that 42% of the patients returned to HAH indicates a high degree of satisfaction with this model of care in our sample.…”
Section: Discussionmentioning
confidence: 99%